The Ukrainian crisis as a factor in accelerating the transition to a bipolar world - Engoyan, Ashot (YSU Journal of International Affairs, 2022)
Since its inception in 2014, the Ukrainian crisis has significantly exacerbated the mutual distrust between Western countries and Russia that has existed since the end of the 20th century. Moreover, in fact, a new stage of “non-contact” confrontation between them has begun, which many politicians and experts call the period of a hybrid war. It is known that it is accompanied not only by the use of complementary political, economic and information measures, but also by the open support of the “fifth columns” operating on enemy territory, or by a combination of covert operations and sabotage with tangible cyber attacks, etc.The sphere of hybrid wars has affected not only Russia, but also a number of other large countries that do not fit into the stencils and parameters of the “democratic platform” designated by the West. One gets the impression that the “civilized world” thinks only of one thing, that is, how to establish democratic orders in authoritarian countries and give the peoples of these countries “true freedom”? However, a detailed analysis of the policy of the “saviors of the world” reveals that simple mercantile interests, or geopolitical goals, aimed at weakening other world centers that are recovering their strength, are hidden behind a beautiful signboard.
Keywords: The Ukrainian crisis; a bipolar world; mutual distrust; a new confrontation; a period of hybrid war; a democratic platform; a civilized world